2006
DOI: 10.1080/11038120500360648
|View full text |Cite
|
Sign up to set email alerts
|

Leaving homelessness and addiction: Narratives of an occupational transition

Abstract: The aim of this exploratory study was to gain an understanding of occupational aspects of homelessness and of the transition from homelessness. Data were collected through narrative interviews of two formerly homeless women recovering from drug addiction. Data were analyzed using a constant comparative method followed by a narrative analysis. The findings first identified homelessness as a life of high intensity lived within a limited time perspective. Further, for these women homelessness was related to drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…The importance of practice was similarly highlighted in a study of leaving homelessness and addiction as an occupational transition (Heuchemer & Josephsson, 2006). Successful transition relied on doing, acting on intent, as described by one participant: "You have to work at your change.…”
Section: Smoking and Quitting As Occupationsmentioning
confidence: 88%
“…The importance of practice was similarly highlighted in a study of leaving homelessness and addiction as an occupational transition (Heuchemer & Josephsson, 2006). Successful transition relied on doing, acting on intent, as described by one participant: "You have to work at your change.…”
Section: Smoking and Quitting As Occupationsmentioning
confidence: 88%
“…The importance of community connection through occupation was echoed in a number of studies (Heuchemer and Josephsson 2005, MacDonald 2006, Schults-Krohn et al 2004, Tryssenaar et al 1999. In most cases social relationships and community affiliations are seen as vital to maintain and support self-respect.…”
Section: A) the Occupational Needs Of People Experiencing Homelessnessmentioning
confidence: 92%
“…They found that supervised methadone consumption was seen as hindering progress to the desired 'normal' life of conventional employment. Heuchemer and Josephsson [10] argued that occupational imbalance is related to the narrowing repertoire of daily occupations that typifies addiction-related behavior. They explain that "an unhealthy balance of daily occupations may lead to an internal conflict between what people should do and what they want to do" [10] (p. 161).…”
Section: Discussionmentioning
confidence: 99%
“…Heuchemer and Josephsson [10] argued that occupational imbalance is related to the narrowing repertoire of daily occupations that typifies addiction-related behavior. They explain that "an unhealthy balance of daily occupations may lead to an internal conflict between what people should do and what they want to do" [10] (p. 161). Participants in this study struggled with this internal conflict; however it was often expressed in terms of what they would want to do versus what they thought they might actually end up doing.…”
Section: Discussionmentioning
confidence: 99%